PENINGKATAN KEMAMPUAN BERBICARA BAHASA INGGRIS MELALUI MODEL QUANTUM LEARNING - HASLAN, HASLAN (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
Quantum Learning is a Model of learning that integrates educational theories and how they are immediately implemented in the class room to form holistically unified learning content which are more relevant and meaningful to students life. This in turn is expected to improve the student responsibility for their own leaning to become more effective life-long learners. The application of the learning model may therefore be expected to enhance effective engagement of the students in the process of learning communicative skills in foreign language. The objective of the study reported here is to conduct an action research to apply the Quantum Learning Model in a Senior High School five Kendari of South East Sulawesi, to improve the students speaking skill in English, involving only the second graders, in second semester of the 2008/2009 academic year. The action research was conducted in the three cycles. The data wens collected through a pretest, a posttest, classroom observation, the students daily Journal, the students portfolio, and Interview with the students as well as the collaborator. They were then analyzed Qualitatively and Quantitatively. No improvement of the students speaking skill was observed In the first cycle, not very significant improvement was observed in the second cycle, and significant improvement was observed in the third cycles, after revision of the teaching learning process were made in first and the second cycles. This indicated the suitability of the Quantum Learning Model to improve school students speaking skills, and hence strongly recommended to be applied at school.Keywords: quantum learning, speaking skill, learning model